2021
DOI: 10.3171/2020.10.jns202779
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of intraoperative visual evoked potential for visual outcome after extended endoscopic endonasal surgery for adult craniopharyngioma

Abstract: OBJECTIVE Due to the proximity of craniopharyngioma to the optic apparatus, one of the most common complications after surgery is visual deterioration. Intraoperative visual evoked potential (VEP), as a means of real-time visual function monitoring, has been integrated into transsphenoidal surgery for pituitary adenoma to predict postoperative visual outcome. Compared with pituitary tumor, craniopharyngioma often adheres to optic nerves, with increased risk of postoperative visual impairment. Furthermore, exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…However, in consideration of age-related changes and sexual difference in OCT parameters, age and gender still needed to be considered in multivariate analysis when using cpRNFL thickness to make clinical prediction models [12,16,1,32]. Moreover, the present study demonstrated that tight adhesion between craniopharyngioma and optic nevers was an independent risk factor for postoperative visual outcome, which was simlair to our previous results [31]. [20], the extended endoscopic endonasal approach can provide a close-up view with better visualization of optic nerves and facilitate a lower visual deterioration after surgery[6, 29,34], probably because there was less surgical trauma.…”
Section: Discussionsupporting
confidence: 75%
“…However, in consideration of age-related changes and sexual difference in OCT parameters, age and gender still needed to be considered in multivariate analysis when using cpRNFL thickness to make clinical prediction models [12,16,1,32]. Moreover, the present study demonstrated that tight adhesion between craniopharyngioma and optic nevers was an independent risk factor for postoperative visual outcome, which was simlair to our previous results [31]. [20], the extended endoscopic endonasal approach can provide a close-up view with better visualization of optic nerves and facilitate a lower visual deterioration after surgery[6, 29,34], probably because there was less surgical trauma.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, visual function worsened in 18.2% of the patients. We also used intra-operative VEP monitoring to assess manipulation of the optic nerve in order to avoid surgical damage to visual function ( 11 ). We also tried to remove more bone from the optical canals to increase the mobilization of the optic chiasm, which can reduce manipulation injuries though TLTA ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…All patients received intraoperative VEP monitoring to predict visual outcomes, as referred to in our previous work ( 11 ). More attention was given to VEP variations during the three stages of unroofing the optic canal, removing the tumor and reconstructing the skull base.…”
Section: Methodsmentioning
confidence: 99%
“…There is increasing evidence suggesting that preoperative OCT parameters can serve as excellent prognostic indicators of visual outcome after surgery for parasellar lesions, such as meningioma, pituitary adenoma, and craniopharyngioma (14,18,(33)(34)(35). Among these tumors, craniopharyngiomas often directly adhere to the undersurface of optic nerves or chiasm, with a higher risk of postoperative visual deterioration (36). Hence, it is helpful for patients with craniopharyngiomas to establish reliable multivariable prediction models to give them good counsel on visual prognosis.…”
Section: Discussionmentioning
confidence: 99%